Clustering in ferronematics: the effect of magnetic collective ordering - Lacková, Veronika; Schroer, Martin A.; Honecker, Dirk; Hähsler, Martin; Vargová, Hana; Zakutanská, Katarína; Behrens, Silke; Kováč, Jozef; Svergun, Dmitri I.; Kopčanský, Peter; Tomašovičová, Natália (iScience, 2021)
Clustering of magnetic nanoparticles can dramatically change their collective magnetic properties, and it consequently may influence their performance in biomedical and technological applications. Owing to tailored surface modification of magnetic particles such composites represent stable systems. Here, we report ferronematic mixtures that contain anisotropic clusters of mesogen-hybridized cobalt ferrite nanoparticles dispersed in liquid crystal host studied by different experimental methods—magnetization measurements, small-angle X-ray scattering (SAXS), small-angle neutron scattering (SANS), and capacitance measurements. These measurements reveal non-monotonic dependencies of magnetization curves and the Fréedericksz transition on the magnetic nanoparticles concentration. This can be explained by the formation of clusters, whose structures were determined by SAXS measurements. Complementary to the magnetization measurements, SANS measurements of the samples were performed for different magnetic field strengths to obtain information on the orientation of the liquid crystal molecules. We demonstrated that such hybrid materials offer new avenues for tunable materials.